Potential Mechanisms of Action of Chinese Patent Medicines for COVID-19: A Review - Yang, Zhi-Hua; Wang, Bin; Ma, Qian; Wang, Lin; Lin, Ya-Xin; Yan, Hai-Feng; Fan, Zi-Xuan; Chen, Hao-Jia; Ge, Zhao; Zhu, Feng; Wang, Hui-Jie; Zhang, Bao-Nan; et al. (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19) is an emergent infectious pneumonia caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which is highly contagious and pathogenic. COVID-19 has rapidly swept across the world since it was first discovered in De-cember 2019 and has drawn significant attention world-wide. During this outbreak, China has been the main battlefield in the early stages of the epidemic and Traditional Chinese Medicines (TCM) have been involved in the whole treatment process. As an indispensable part of TCM, Chinese patent medicines (CPMs) have played an irreplaceable role in the prevention and treat-ment of this epidemic. Their use has achieved remarkable therapeutic efficacy during the period of medical observation and clinical treatment of mild, moderate, severe, and critical cases and during convalescence. In order to better propagate and make full use of the benefits of TCM in the treatment of COVID-19, this review will summarize the potential target of SARS-CoV-2 as well as the theoretical basis and clinical efficacy of recommended 22 CPMs by National Health Commission and the Administration of TCM and local provinces or cities in the treatment of COVID-19. Additionally, the study will further analyze the drug composition, potential active ingredients, potential targets, regulated signaling pathways and possible mechanisms for COVID-19 through anti-inflammatory and immunoregulation, antiviral, improve lung injury, antipyretic and o to provide meaningful information about the clinical application of CPMs.